Sky Bus Project of Konkan Railway: Will it see the Light of the Day? - Sidhpuria, M. V.; Wani, Nitin (Gyan Management Journal, 2008)
The present challenge for KRCL is to market the technologies it has developed and obtain the world patent. - Dr K. K. Gokhale, MD, Konkan Railway Corporation Dr. Ketan Kamalakar Gokhale who has succeeded Mr. B Raja Ram· as MD of Konkan Railway (KR) was brooding over the issue of capitalizing the intellectual capital, which KR has in the form of patents for Anticollision device & especially the Sky Bus technology. Dr. Gokhale, IRTS 1970 batch, was instrumental in establishing and developing Rol1-on-Roll-off (RoRo) services, Railotels at Kumta and Ratnagiri, rail based tourism packages as well as improving the level of services on Konkan Railway. [During his tenure the revenue from Coaching and Freight of KR has increased from Rs.118.13 crores (1999-2000) to Rs.235.36 crores (2003-2004).]. However, he was quite worried about the Sky Bus Project of KR. He was wondering whether KR would be able to capitalize on its Sky Bus Technology.